Summer of the monkeys - Rawls, Wilson (New York Bantam Doubleday Dell Books for Young Readers, 1999)
In the late 1800s, a fourteen-year-old Ozark mountain boy spends the summer trying to recapture monkeys escaped from a traveling circus.
"A Yearling book."
810L
93652
Keywords: Monkeys; Oklahoma